(untitled) (Élisée - Revista de Geografia da UEG, 2021)
This article presents necessary reflections on the subject: education for ethnic-racial relations, through the use of esthetic elements, in school and academic environment, such as Ojá. From the use of active methodology to carry out pedagogical interventions with the use of Ojás, turbans used by black African women and in diaspora, we set ourselves to think about the impacts of racism as a system of domination, approaching the processes of construction of the black esthetics and identity as promoters of redefinition and appreciation of black self-esteem. We consider the symbolic relevance of Orí, the head receiving Ojá, as an important field for interpreting Afro-descendant experiences in Brazil. From the conversation circle methodology, we had the participation of young people from several different ethnic-racial backgrounds from high school and university from public institutions in the State of Goiás. Based on the themes worked on in the conversation circles, it was possible to list methodological content and practices towards an anti-racist education based on readings of Geography and History, also knowing the plots that involve the processes of (re)construction, self-affirmation of black identity. and ratify the self-esteem of the black people.